Efektivitas Intervensi Stretching Dengan Menggunakan Video Terhadap Penurunan Intensitas Low Back Pain Pada Mahasiswa Fakultas Keperawatan Universitas Riau Di Masa Pandemi Covid-19 - Rosa Prestika Sari; Yufitriana Amir; Rismadefi Woferst (Yayasan Jompa Research and Development, 2022)
Introduction: During the Covid-19 pandemic, all levels of education were conducted online or remotely. Students do online learning and must be in front of computer screen until the duration of the lecture is over. This causes students to complain of several complaints such as neck, shoulder, hand, back, waist and leg pain. These symptoms can be overcome by doing activities that can relax the muscles such as stretching. Objective: This study aims to determine the effectiveness of the stretching intervention on reducing the intensity of low back pain in students of the Faculty of Nursing, University of Riau during the Covid-19 pandemic. Methods: This study uses the Quasi Experiment method with a one group pretest-posttest research design. The sample in this study amounted to 34 people who were taken based on the inclusion criteria set by the researcher using purposive random sampling. This research was conducted using an observation sheet. The analysis used is univariate analysis and bivariate analysis of dependent t test. Results: The average result of the student's pain intensity before being given a stretching intervention was 3.82 and the average pain intensity after being given a stretching intervention was 1.68 with a p value of 0.000 < 0.05. Conclusion: Stretching intervention using video is effective in reducing the intensity of low back pain in students of the Faculty of Nursing, University of Riau. Keywords: Covid-19;stretching;low back pain;pain intensity;students